Measuring Medicine Use: Applying ATC/DDD Methodology to Real-World Data - Samantha Hollingworth; Therése Kairuz (MDPI AG, 2021)
Medicines are essential for the treatment of acute, communicable, and non-communicable diseases. The World Health Organization developed a toolkit for drug (medicine) utilization studies to assist in reviewing and evaluating the prescribing, dispensing, and use of medicines. There is a growing need for rigorous studies of medicine use in low- and middle-income countries (LMIC) using standard approaches, especially in the context of universal health coverage. This commentary provides a succinct summary of how to use the WHO anatomical therapeutic chemical (ATC)/defined daily dose (DDD) methodology in pharmacoepidemiological studies, with a focus on LMIC contexts. We drew on information from WHO resources and published literature, citing examples and case studies. We encourage readers to publish their drug utilization studies, although we caution about predatory journals. We recommend the use of the RECORD-PE initiative which focuses on methods for doing pharmacoepidemiological research and evaluating the quality of published papers.